Of earth and sky: A pair of Ming hanging scrolls, from past repairs to present conservation - Stiglitz, M; Bearman, J (De Gruyter, 2016)
A pair of Chinese scrolls representing the earth and sky were donated to the Bodleian Library in 1684. They are thought to be ephemeral items printed during the late Ming dynasty. Records indicate that in 1883 the scrolls were trimmed, patched with transparent paper, backedwith cloth andmounted in an unsympathetic manner. In this paper,weconsider the conservation and preservation measures adopted by the then Bodleian Librarian and reflect on his participation at the St. Gall Conference in 1898. The conservation treatment of the scrolls completed in 2015was guided by their past repairs, current ethical considerations and scientific analysis. Breaking the strong bond between the transparent paper and the fragile surface of the scrolls required experimentation with the Albertina Compress and Gellan gum. The recreation of functional hanging scrolls involved the use of traditional scroll-mounting techniques and the reinterpretation of the Chinese mounting style from a western conservation perspective. We also discuss the experience gained in treating two artefacts with almost identical problems.